Discourses on ag(e)ing individuals, social inequality, and the effects of social distancing in times of covid-19 - Mazuchelli, Larissa Picinato; Soares, Maria Francisca de Paula; Noronha, Diana Oliveira; Oliveira, Marcus Vinicius Borges (Saúde e Sociedade, 2021)
Our work discusses the effects of covid-19 on older adults’ health, which is considered the leading risk group in this pandemic. We start with a brief ag(e)ing demographic discussion in Brazil and then address how this period has produced and reinforced discourses that show ag(e)ing stereotypes. These discourses are related to the difficulties in facing the social distancing effects and its possibilities in the context of residential care and in long-term institutions in the state of Bahia, Brazil, where we centralize this discussion. To conclude, we emphasize the urgency of organized and coordinated actions that understand the ag(e)ing process complexity to face both the prejudiced discourses about older adults and the effects of isolation. We also point to the need to recognize and involve ourselves in the other generations of which we are a part, whether in memory or projection.